Did Globalization Influence Credit Market Deregulation - Peter Eppinger; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate whether globalization influenced credit market deregulation over the period 1970-2010. Globalization is measured by the KOF indices of globalization. Credit market deregulation is measured by the credit market freedom indicators of the Fraser Institute. The results from both cross-sectional and panel regressions using ordinary least squares indicate a positive correlation between globalization and credit market deregulation. We account for reverse causality by using predicted trade openness as an instrumental variable and show that this approach gives rise to different conclusions. Two-stage least squares estimations do not show that globalization had a causal influence on credit market deregulation.
Keywords: F65; F68; G18; G28; F42; C26; 330; globalization; credit market deregulation; instrumental variables